First detection of infectious haematopoietic necrosis virus in farmed rainbow trout in North Macedonia - Cvetkovikj, Aleksandar; Radosavljevic, Vladimir; Cuenca, Argelia; Strojmanovska, Biljana; Maksimovic-Zoric, Jelena; Cvetkovikj, Iskra; Olesen, Niels Jørgen (Inter-Research Science Center, 2020)
Infectious haematopoietic necrosis virus (IHNV) is the causative agent of infectious haematopoietic necrosis (IHN), a disease of salmonids responsible for great economic losses. The disease occurs in most parts of the world where rainbow trout is reared but has not been previously reported in North Macedonia. In this study, 150 pooled samples in total, each consisting of organ mix of 10 freshly killed rainbow trout Oncorhynchus mykiss, were collected from 50 trout farms by the Food and Veterinary Agency of North Macedonia as part of the annual surveillance plan for IHN and viral haemorrhagic septicaemia (VHS) control. Screening of samples was done by cell culture and real-time RT-PCR (qRT-PCR). All 150 tested samples were VHS virus (VHSV) qRT-PCR negative. Two samples from different trout farms were IHNV qRT-PCR positive. On cell culture, 1 IHNV qRT-PCR positive sample caused cytopathic effect after 2 passages on EPC cells. The virus, isolated from an asymptomatic rainbow trout fry, was identified by qRT-PCR and designated as MAKIHNV1. The phylogenetic reconstruction indicates that the isolated virus belongs to the European E genogroup, more specifically within the E-1 clade, and is similar to the German, Italian and Iranian isolates. This study has revealed for the first time the presence of IHNV in rainbow trout in North Macedonia. However, it is not possible to make interpretations about the source of infection from the phylogenetic analysis, and the origin of MAKIHNV1 remains unclear.
Keywords: Infectious haematopoietic necrosis virus · IHNV · Rainbow trout · Phylogeny